2019
DOI: 10.1016/j.oceaneng.2019.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of hull roughness

Abstract: In this paper we present a practical guideline on how to estimate the frictional resistance of ship hulls due to different fouling control coatings. Most of the current methods rely on empirical formulations based on an equivalent sand grain roughness height. These correlations are not universal and cannot be applied to every marine surface. Conversely, the shear stress of a specific coating can be measured in an experimental facility at the same Reynolds roughness number as at full scale. The results can be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…in CFD simulations (Demirel b et al, 2017, Farkas b et al, 2018, Speranza et al, 2019, Song c et al, 2019. The merit of using CFD simulations is that it allows determination of the roughness effect on every resistance component (Song c et al, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…in CFD simulations (Demirel b et al, 2017, Farkas b et al, 2018, Speranza et al, 2019, Song c et al, 2019. The merit of using CFD simulations is that it allows determination of the roughness effect on every resistance component (Song c et al, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…The analyses performed for model scale flat plate, full-scale flat plate and full-scale KCS hull. Similar studies focussing on modelling the roughness in CFD can be found in [51,52], [53], [54] and [55].…”
Section: Introductionmentioning
confidence: 71%
“…A sensitivity analysis with different fluid speeds and surface roughness was then done employing the flat field. The reproduction of surface roughness is defined through an equivalent sand grain diameter (k s ) [30][31][32][33]. The scaleequipped plate with most promising results in terms of drag reduction in the first analysis was considered as the fixed scale model; in Appendix 3, the model was adopted to relate surface roughness with the sand grain diameter.…”
Section: Effect Of Scale Design and Surface Roughness On Water Dragmentioning
confidence: 99%